2015
DOI: 10.3390/e17074563
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Cosmological Application of Some Thermodynamic Properties of the Black Body Radiation in n-Dimensional Euclidean Spaces

Abstract: In this work, we present the generalization of some thermodynamic properties of the black body radiation (BBR) towards an n-dimensional Euclidean space. For this case, the Planck function and the Stefan-Boltzmann law have already been given by Landsberg and de Vos and some adjustments by Menon and Agrawal. However, since then, not much more has been done on this subject, and we believe there are some relevant aspects yet to explore. In addition to the results previously found, we calculate the thermodynamic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(73 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…We will show that the efficiency for a blackbody radiation cycle is calculated by the same formula as that for an ideal gas in a Carnot cycle, i.e., e CARNOT = (1 -TC/ TH). This result has been confirmed independently in another and earlier work [15] , in the context of defining thermodynamic variables for a blackbody in n-spatial dimensions. We also give the total work done which will drive the expansion/contraction process over a complete cycle, W = |QH| -|QC|, which also confirms a previous result [16] .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…We will show that the efficiency for a blackbody radiation cycle is calculated by the same formula as that for an ideal gas in a Carnot cycle, i.e., e CARNOT = (1 -TC/ TH). This result has been confirmed independently in another and earlier work [15] , in the context of defining thermodynamic variables for a blackbody in n-spatial dimensions. We also give the total work done which will drive the expansion/contraction process over a complete cycle, W = |QH| -|QC|, which also confirms a previous result [16] .…”
Section: Introductionsupporting
confidence: 76%
“…Coming back to our Carnot cycle, in going from point b to point c, we expect pb Vb 4/3 = pc Vc 4/3 (adiabatic process) (15) And also, pb/p0 = (a0/ab) 4 = (1+Zb) 4 (adiabatic process) (16)…”
Section: Thermodynamics Of the Early Universementioning
confidence: 99%
“…In a previous work [4] we showed that the thermodynamic potential densities have regions of minima and maxima when we consider isothermal processes. In Figure 1 the critical points of u (n, T ), f (n, T ) and s (n, T ) with respect to the dimension n (∂ n u, f, s = 0) are shown.…”
mentioning
confidence: 84%
“…The rest of the potential densities s, f , and also the internal energy density u are functions depending on the absolute temperature T and the dimensionality n. When all these functions were plotted against T and n they seemingly did not show any interesting feature [4]. However, when a zoom was made in the region of very high temperatures (of the order of Planck's temperature T P ) and low dimensionality (in the interval nǫ(1, 10)), a very surprising behavior was observed [4]. On the other hand, it is well established that at early times, long before the time of radiation-matter equality, the universe could have been well described by a spatially flat, radiation-only model [5].…”
mentioning
confidence: 98%
See 1 more Smart Citation